1999
DOI: 10.1021/ja9903025
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Bonded Self-Assembled Peptide Nanotubes from Cystine-Based Macrocyclic Bisureas

Abstract: The design, synthesis, and characterization of amino acid-based cyclic bisureas, a new class of macrocyclic peptides, are described. These cystine-based macrocycles are constructed by a single-step procedure involving condensation of 1,ω-alkane diisocyanate[(CH2) n (NCO)2; n = 4, 6, 12] with either the simple l-cystine dimethyl ester to provide simple cyclic bisureas of 16-, 18-, and 24-membered rings through 1 + 1 cyclization or with extended cystine bispeptides leading to a variety of cystine-based macrocycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(71 citation statements)
references
References 10 publications
0
66
0
5
Order By: Relevance
“…We envisioned that the bis-urea motif could be utilized as a hydrogen-bonding unit in self-assembled (salen)Co catalysts for HKR of epoxides (Scheme 1). Because N,N'-disubstituted ureas can provide directional hydrogen-bonding interactions between two NH protons and the carbonyl group, [20] the urea motif has been widely applied to the construction of supramolecular architectures such as columns, [21] capsules, [22] nanotubes, [23] channels, [24] supramolecular polymers, [25] and organogels. [26] Furthermore, some bis-and tetra-urea structures have shown self-assembly in polar media such as THF or even in aqueous solution through the combination of hydrogen-bonding and hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…We envisioned that the bis-urea motif could be utilized as a hydrogen-bonding unit in self-assembled (salen)Co catalysts for HKR of epoxides (Scheme 1). Because N,N'-disubstituted ureas can provide directional hydrogen-bonding interactions between two NH protons and the carbonyl group, [20] the urea motif has been widely applied to the construction of supramolecular architectures such as columns, [21] capsules, [22] nanotubes, [23] channels, [24] supramolecular polymers, [25] and organogels. [26] Furthermore, some bis-and tetra-urea structures have shown self-assembly in polar media such as THF or even in aqueous solution through the combination of hydrogen-bonding and hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The size and shape of the ring will determine the pore diameter of resulting tubes. Well-known macrocycles include cyclic peptides [65], cyclic oligosaccharides [66], and cyclic multiureas [67], of which cyclic bis/tetraureas are more efficient to form 1D independent tubes in solid state. In 1999, Ranganathan and coworkers [67] prepared an amino acid-based cyclic bisurea 32 and characterized its assembly by single-crystal X-ray studies (Fig.…”
Section: Tubes Constructed From Flat Macrocyclesmentioning
confidence: 99%
“…In a recent study, [5] our groups found that the medium in which the self-assembly of cyclic peptides takes place may have a profound effect on the final structure. Instead of forming a compact crystal in organic solvents, a macrolactam, namely, cyclo(NHCH 2 CH=CHCH 2 CO) 3 (E olefin), dissolved in a nematic liquid crystal (LC) formed micrometer-sized hexagonal hollow tubes on slow cooling of the mixture. The intermolecular interaction between the cyclic peptide and the medium, that is, the liquid crystal in this case, is no doubt a decisive factor that caused the dramatic change in the self-assembled structure of the peptide.…”
Section: Introductionmentioning
confidence: 99%